Progress of Nanomaterials in Photodynamic Therapy Against Tumor - Chen, Lei; Huang, Jiahui; Li, Xiaotong; Huang, Miaoting; Zeng, Shaoting; Zheng, Jiayi; Peng, Shuyi; Li, Shiying (Frontiers in Bioengineering and Biotechnology, 2022)
Photodynamic therapy (PDT) is an advanced therapeutic strategy with light-triggered, minimally invasive, high spatiotemporal selective and low systemic toxicity properties, which has been widely used in the clinical treatment of many solid tumors in recent years. Any strategies that improve the three elements of PDT (light, oxygen, and photosensitizers) can improve the efficacy of PDT. However, traditional PDT is confronted some challenges of poor solubility of photosensitizers and tumor suppressive microenvironment. To overcome the related obstacles of PDT, various strategies have been investigated in terms of improving photosensitizers (PSs) delivery, penetration of excitation light sources, and hypoxic tumor microenvironment. In addition, compared with a single treatment mode, the synergistic treatment of multiple treatment modalities such as photothermal therapy, chemotherapy, and radiation therapy can improve the efficacy of PDT. This review summarizes recent advances in nanomaterials, including metal nanoparticles, liposomes, hydrogels and polymers, to enhance the efficiency of PDT against malignant tumor.